DEVELOPING WORDWALL-BASED LEARNING MEDIA FOR ONLINE BUSINESS SUBJECTS FOR ELEVENTH GRADE STUDENTS AT SMKN 1 SOOKO MOJOKERTO - Ningrum, Ananda Octavia; Sulistyowati, Raya (Universitas Negeri Surabaya, 2024)
Phenomenon/Issue: The issue addressed in the study is the need for effective learning media for the Online Business subject for Eleventh-grade students at SMKN 1 Sooko Mojokerto. Purpose: The purpose of the study is to develop Wordwall-based learning media to enhance the learning process for Online Business subjects for Eleventh-grade students at SMKN 1 Sooko Mojokerto. Novelty: The novelty of the study lies in the development of Wordwall-based learning media, which integrates interactive and engaging tools to facilitate Online Business learning, specifically designed for SMKN 1 Sooko Mojokerto's eleventh-grade students.. Research Methods: This study used the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The study involved 34 students from the eleventh Online Business and Marketing class at SMKN 1 Sooko Mojokerto. Validation of the media was conducted by three experts: a linguist, a media expert, and a material expert Results: The validation results indicated that the Wordwall-based learning media is highly feasible, with language validation at 82%, media validation at 98%, and material validation at 100%. These findings suggest that the learning media is highly suitable for Online Business learning at SMKN 1 Sooko Mojokerto. Research Contributions: This study contributes by providing a validated and suitable Wordwall-based learning media for Online Business subjects, offering an effective tool for enhancing student engagement and improving learning outcomes in the eleventh-grade class at SMKN 1 Sooko Mojokerto